Clinical outcomes of patients with and without HIV hospitalized with COVID‐19 in England during the early stages of the pandemic: a matched retrospective multi‐centre analysis (RECEDE‐C19 study). Issue 2 (23rd September 2021) - Lee, Ming Jie; Snell, Luke Blagdon; Douthwaite, Sam T.; Fidler, Sarah; Fitzgerald, Naomi; Goodwin, Lynsey; Hamzah, Lisa; Kulasegaram, Ranjababu; Lawrence, Sarah; Lwanga, Julianne; Marchant, Rebecca; Orkin, Chloe; et al.
Abstract: Background: The contribution of HIV to COVID‐19 outcomes in hospitalized inpatients remains unclear. We conducted a multi‐centre, retrospective matched cohort study of SARS‐CoV‐2 PCR‐positive hospital inpatients analysed by HIV status. Methods: HIV‐negative patients were matched to people living with HIV (PLWH) admitted from 1 February 2020 to 31 May 2020 up to a 3:1 ratio by the following: hospital site, SARS‐CoV‐2 test date ± 7 days, age ± 5 years, gender, and index of multiple deprivation decile ± 1. The primary objective was clinical improvement (two‐point improvement or better on a seven‐point ordinal scale) or hospital discharge by day 28, whichever was earlier. Results: A total of 68 PLWH and 181 HIV‐negative comparators were included. In unadjusted analyses, PLWH had a reduced hazard of achieving clinical improvement or discharge [adjusted hazard ratio (aHR) = 0.57, 95% confidence interval (CI): 0.39–0.85, p  = 0.005], but this association was ameliorated (aHR = 0.70, 95% CI: 0.43–1.17, p  = 0.18) after additional adjustment for ethnicity, frailty, baseline hypoxaemia, duration of symptoms prior to baseline, body mass index (BMI) categories and comorbidities. Baseline frailty (aHR = 0.79, 95% CI: 0.65–0.95, p  = 0.011), malignancy (aHR = 0.37, 95% CI 0.17, 0.82, p  = 0.014) remained associated with poorer outcomes. The PLWH were more likely to be of black, Asian and minority ethnic background (75.0% vs 48.6%, p  = 0.0002), higher median clinical frailty score [3 × interquartile range (IQR): 2–5 vs, 2 × IQR: 1–4, p  = 0.0069), and to have a non‐significantly higher proportion of active malignancy (14.4% vs 9.9%, p  = 0.29). Conclusions: Adjusting for confounding comorbidities and demographics in a matched cohort ameliorated differences in outcomes of PLWH hospitalized with COVID‐19, highlighting the importance of an appropriate comparison group when assessing outcomes of PLWH hospitalized with COVID‐19.